2006
DOI: 10.4049/jimmunol.177.8.5574
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Regulates Blood-Brain Barrier Permeability via Reactivation of the Hypoxia-Angiogenesis Program

Abstract: Loss of blood-brain barrier (BBB) integrity is believed to be an early and significant event in lesion pathogenesis in the inflammatory demyelinating disease multiple sclerosis (MS), and understanding mechanisms involved may lead to novel therapeutic avenues for this disorder. Well-differentiated endothelium forms the basis of the BBB, while astrocytes control the balance between barrier stability and permeability via production of factors that restrict or promote vessel plasticity. In this study, we report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
221
3
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 302 publications
(238 citation statements)
references
References 65 publications
(81 reference statements)
9
221
3
5
Order By: Relevance
“…Recently, we investigated potential links between astrocyte reactivity and BBB breakdown. Compatible with reports from other groups, our results implicated the transcription factor hypoxia-inducible factor-1␣ and its effector VEGF-A in these events (16). VEGF-A is the most important angiogenic factor in the developing CNS (17,18) and a potent inducer of BBB disruption in adults (19,20).…”
supporting
confidence: 56%
See 3 more Smart Citations
“…Recently, we investigated potential links between astrocyte reactivity and BBB breakdown. Compatible with reports from other groups, our results implicated the transcription factor hypoxia-inducible factor-1␣ and its effector VEGF-A in these events (16). VEGF-A is the most important angiogenic factor in the developing CNS (17,18) and a potent inducer of BBB disruption in adults (19,20).…”
supporting
confidence: 56%
“…Its signal-transducing receptor Flk-1/VEGFR2 is expressed by BMVECs (16), and homozygous Flk-1/VEGFR2 -/-mice exhibit a similar phenotype to that of VEGF-A mutants and die in utero (26). Mice homozygous for loss of the non-signal-transducing receptor Flt-1/VEGFR1 show excessive disorganized endothelium and are also nonviable (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we detected only moderate increases in pro-inflammatory cytokine levels, the long term effects of chronic endothelial activation combined with low-level production of pro-inflammatory cytokines likely culminates in reduced vascular integrity with detrimental consequences. Indeed inflammatory mediators such as IL-1β, TNFα and IL-6 have been shown to have a prominent role in blood-brain barrier disruption (Abbott, 2000;Argaw et al, 2006). Though the mechanisms by which they act remain largely unclear, it has been suggested that IL-1β affects paracellular permeability while TNFα increases transcellular permeability (Abbott, 2000).…”
Section: Discussionmentioning
confidence: 99%